With complements: C3 inhibition in the clinic. Issue 1 (25th September 2022) - Kolev, Martin; Barbour, Tara; Baver, Scott; Francois, Cedric; Deschatelets, Pascal
Summary: C3 is a key complement protein, located at the nexus of all complement activation pathways. Extracellular, tissue, cell‐derived, and intracellular C3 plays critical roles in the immune response that is dysregulated in many diseases, making it an attractive therapeutic target. However, challenges such as very high concentration in blood, increased acute expression, and the elevated risk of infections have historically posed significant challenges in the development of C3‐targeted therapeutics. This is further complicated because C3 activation fragments and their receptors trigger a complex network of downstream effects; therefore, a clear understanding of these is needed to provide context for a better understanding of the mechanism of action (MoA) of C3 inhibitors, such as pegcetacoplan. Because of C3's differential upstream position to C5 in the complement cascade, there are mechanistic differences between pegcetacoplan and eculizumab that determine their efficacy in patients with paroxysmal nocturnal hemoglobinuria. In this review, we compare the MoA of pegcetacoplan and eculizumab in paroxysmal nocturnal hemoglobinuria and discuss the complement‐mediated disease that might be amenable to C3 inhibition. We further discuss the current state and outlook for C3‐targeted therapeutics and provide our perspective on which diseases might be the next success stories in the C3 therapeutics journey.